2015
DOI: 10.1002/jmv.24357
|View full text |Cite
|
Sign up to set email alerts
|

HBV‐DNA levels predict overall mortality in HIV/HBV coinfected individuals

Abstract: The coinfection of Hepatitis B virus (HBV) and human immunodeficiency virus (HIV) has been associated with increased death rates. However, the relevant research has mostly relied on serologic HBV testing [HBV surface antigen (HBsAg)]. The aim of this work was to explore the relationship of HBV viraemia with overall mortality among HIV/HBV coinfected individuals. The analysis included 1,609 HIV seropositives of a previously described cohort (1984-2003) with limited exposure to tenofovir (12%) and a median follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Routine Hepatitis B screening is essential in the evaluation and management of HIV patients. Elevated HBV DNA level is associated with overall mortality in HBV/HIV co-infected patients, especially during the period before development of AIDS [ 30 ], and it is essential to identify patients who have viremia for treatment intensification. Majority of ART-naïve (89 %) and 42 % of ART-experienced patients were found to have detectable HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Routine Hepatitis B screening is essential in the evaluation and management of HIV patients. Elevated HBV DNA level is associated with overall mortality in HBV/HIV co-infected patients, especially during the period before development of AIDS [ 30 ], and it is essential to identify patients who have viremia for treatment intensification. Majority of ART-naïve (89 %) and 42 % of ART-experienced patients were found to have detectable HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our sampling procedures were performed in the AIDS clinic, and our study population consisted of regularly attending outpatients in good clinical condition with a high rate of adherence to ART (87.3%), which they had been receiving for a median of six years. Other studies of PLWH outpatients have reported comparable prevalence rates ranging from 6.7% to 11.5% [25,26,35] and, assuming that HIV/HBV co-infected patients experience a faster clinical evolution than other PLWH, it is possible that a disproportional number of coinfected patients were not enrolled [14,27,29]. Third, it cannot be excluded that mortality among the co-infected may have been higher than in the PLWH population as a whole, thus leading to a lower prevalence of HBV among the survivors.…”
Section: Plos Onementioning
confidence: 96%
“…whole Northern Uganda [6]. However, coinfection prevalence was similar to the prevalence of HBV co-infection in Europe [18,[27][28][29], North America [12,30], and even in sub-Saharan Africa [31], where the reported ranges are wider than in Western countries and can reach 36% [5]. In countries where HBV is highly endemic, most cases of infection are attributable to vertical or horizontal transmission during early childhood [23,[32][33][34], although the findings of a recent study challenge the predominant role of vertical transmission in the area of Gulu [35].…”
Section: Plos Onementioning
confidence: 97%
“…Incidence of hepatic fibrosis (14.2%) and cirrhosis (9.2%) is more likely to occur in HIV/HBV co-infection patients [28][29][30][31] and the liver-related mortality in these patients was 8 times higher than that in HIV monoinfection patients [2,32]. Besides, HIV/HBV coinfection is a risk factor for in-hospital mortality [33], which also heightened overall mortality rates (Incidence Rate Ratio: 1.24) [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%